Estimation of the cost-effectiveness of apixaban versus vitamin K antagonists in the management of atrial fibrillation in Argentina - Mariano Anibal Giorgi; Christian Caroli; Norberto Damian Giglio; Paula Micone; Eleonora Aiello; Cristina Vulcano; Julia Blanco; Bonnie Donato; Joaquin Mould Quevedo (Health Economics Review, 2015)
Apixaban, a novel oral anticoagulant which has been approved for the prevention of stroke and systemic embolism in non-valvular atrial fibrillation, reduces both ischemic and haemorrhagic stroke and produces fewer bleedings than vitamin K antagonist warfarin. These clinical results lead to a decrease in health care resource utilization and, therefore, have a positive impact on health economics of atrial fibrillation. The cost-effectiveness of apixaban has been assessed in a variety of clinical settings and countries. However, data from emergent markets, as is the case of Argentina, are still scarce. We performed a cost-effectiveness analysis of apixaban versus warfarin in non-valvular atrial fibrillation (NVAF) in patients suitable for oral anticoagulation in Argentina. A Markov-based model including both costs and effects were used to simulate a cohort of patients with NVAF. Local epidemiological, resource utilization and cost data were used and all inputs were validated by a Delphi Panel of local experts. We adopted the payer's perspective with costs expressed in 2012 US Dollars. The study revealed that apixaban is cost-effective compared with warfarin using a willingness to pay threshold ranging from 1 to 3 per capita Gross Domestic Product (11558 - 34664 USD) with an incremental cost-effectiveness ratio of 786.08 USD per QALY gained. The benefit is primarily a result of the reduction in stroke and bleeding events. The study demonstrates that apixaban is a cost-effective alternative to warfarin in Argentina.
Keywords: 330; Apixaban; Warfarin; Novel oral anticoagulants; Cost-effectiveness